Pengaruh Idiosinkratik Nicolas Maduro Terhadap Penolakan Bantuan Kemanusiaan Amerika Serikat Dalam Krisis Venezuela - Amalia Safira Ashidiqi; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This research discusses the refusal of humanitarian assistance conducted by Venezuelan president Nicolas Maduro of humanitarian aid from donor countries, especially the United States. Although, the refusal of aid was considered inappropriate in the midst of the ongoing humanitarian crisis. Whereas from Maduro's perspective the decision is the right way to protect Venezuela from the influence and interests of the United States. The decission making process of a leader has to do with psychological factors. In the process of decision making, the leader has many characteristics that are considered to shape the decision. Idiosyncratic. Therefore, the formulation of the problem in this study is how is the idiosyncratic influence on the refusal of Venezuelan humanitarian assistance to America? This research has a focus on individual analysis and idiosyncratic theoretical framework that explains the type of leader in making decisions. The results through indicators and analysis of news media interview data, Maduro included in one type of leader whose decisions are much influenced by the characteristics of that type.